E-051 Classification of Cavernous Internal Carotid Artery Tortuosity: A Predictor of Procedural Complexity in Pipeline Embolization. (26th July 2014) - Uwandu, C; Lin, L; Colby, G; Huang, J; Tamargo, R; Coon, A
Abstract : Background: Endoluminal reconstruction of a diseased parent artery with flow diverters is increasingly used for the treatment of intracranial aneurysms. The complexity of these procedures can be highly variable. Understanding the degree of tortuosity of the cavernous internal carotid artery (ICA) may help predict procedural complexities of deploying flow diverters such as the Pipeline embolization device (PED). Methods: We retrospectively reviewed a prospective, single-center aneurysm database to identify all patients with ICA aneurysms proximal to the posterior communicating artery who underwent endovascular treatment using the PED with the Navien distal intracranial guide catheter. Cavernous ICA (cICA) tortuosity was measured as a ratio between the height difference of the cICA anterior and posterior genus (D) to the sum of the angles of the anterior and posterior genus (AP). Identified patients were categorized into three groups based on cICA tortuosity. An analysis of variance regression was performed to detect differences among the three groups as they relate to procedural fluoroscopy time length, cICA tortuosity (D/AP), and aneurysm size. Results: Seventy-eight cICA were analyzed and the degree of tortuosity was categorized into minimal (group I, n = 26), moderate (group II, n = 28), and severe or "Simmons-type" (group III, n = 24). The three groups were comparable with relation to patient age (mean group I – 55.5, II – 55.0, III – 55.9) and aneurysm size (mean group I – 6.2 mm, II – 7.8 mm, III – 9.0 mm). Analysis of variance demonstrated significant differences in procedural fluoroscopy time (FT) and degree of cICA tortuosity (D/AP). Mean FT was greater in group III (50.3 + 13.5) compared to group II (42.3 + 33.3) and group I (30 + 8.4), p value <0.005. Similarly, mean D/AP was significantly higher in group III (0.49 + 0.38) compared to groups II (0.14 + 0.07) and I (0.008 + 0.0008), p value <0.005. In group I, PED deployment was successful in 100% of cases whereas groups II and III had 2 and 1 unsuccessful cases respectively. Conclusion: In this study, we propose a classification system for cICA tortuosity based on measurements of the anterior and posterior genu geometry. This classification correlates strongly with markers of PED procedural complexity and may be helpful in pre-procedure prognostication. Disclosures: C. Uwandu: None. L. Lin: None. G. Colby: None. J. Huang: None. R. Tamargo: None. A. Coon: 2; C; ALC is a proctor for the Pipeline Embolization Device (Covidien, Mansfield, Massachusetts, USA) and a consultant for Covidien.